Contemporary national movement and the problem of migration - Radomski, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to present the position of the contemporary national movement towards the problem of the influx of immigrants to Europe, with a particular emphasis on the threats arising from this fact for Poland. The article uses opinion journalism, political programmes and the press of the contemporary national movement. Content analysis and, to a lesser extent, comparative studies were used as a research method.
Keywords: contemporary national movement; migration; political thought; cultural security; refugees